Reading as Experience: Literature, Response and Imagination. Issue 1 (2nd January 2016) - Lee, Klaudia Hiu Yen; Patkin, John
Abstract: This article uses the findings from an empirical study on Hong Kong students' reading practices as collected through face-to-face interviews on major university campuses in Hong Kong to argue for the importance of affective and imaginative engagement with literary texts if students are to develop an interest in reading. Until now, few empirical studies have been conducted to investigate the actual interaction between the text and student readers, especially in situations that go beyond the usual classroom contexts. This student-centred narrative inquiry, which is grounded in literary and language research, demonstrates that while the notion of relevance, in terms of students' socio-cultural background and their own life experiences, has long been considered as a key factor in the choice of texts used in a literature classroom, it is important to recognize the creativity that is embedded in students' reading processes.